Caracterização das propriedades físico-químicas, bioquímicas e farmacológicas do Baru (Dipteryx alata) e Bacuri (Platonia insignis) - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The use of medicinal plants, their extracts and isolated substances (active principle) is a culture that although ancient is increasingly on the rise in the present day. In this sense, two typical Brazilian fruit have been highlighted for its beneficial properties yet unexplored: the Baru and Bacuri. The baru (Dipteryx alata), belongs to the family Faboideae, the plant has great potential economic because of its multiple uses. Traditionally, locals use the oil extracted from almond to treat high fevers, and also for snake bites. Bacuri (Platonia insignis), for another perspective, is a native fruit species of Pará (Eastern Amazonia), belonging to the Clusiaceae family. The bacuri butter, obtained from oil seeds, is widely used for its anti-inflammatory action. From these reports it became necessary to review information about the popular use of these fruits and determine which have scientific proof, in addition to classify a material that features these by their physicochemical properties, biochemical and pharmacological, and other information as botanical characteristics, nutritional composition, occurrence in Brazil and its popular use. The results obtained include satisfactorily to these issues, as it is expected that further studies using products or by-products of baru and bacuri are developed with greater theoretical background on them.
Keywords: Alimentos funcionais; Antioxidantes; Ação anti-inflamatória; Functional foods; Antioxidants; Anti-inflammatory action; CNPQ::CIENCIAS EXATAS E DA TERRA